Prevalence of respiratory viruses and antiviral MxA responses in children with febrile urinary tract infection - Piri Ruut; Ivaska Lauri; Yahya Mohamed; Toivonen Laura; Lempainen Johanna; Kataja Janne; Nuolivirta Kirsi; Tripathi Lav; Waris Matti; Peltola Ville (SPRINGER, 2022)
Blood myxovirus resistance protein A (MxA) has broad antiviral activity, and it is a potential biomarker for symptomatic virus infections. Limited data is available of MxA in coinciding viral and bacterial infections. We investigated blood MxA levels in children hospitalized with a febrile urinary tract infection (UTI) with or without simultaneous respiratory virus infection. We conducted a prospective observational study of 43 children hospitalized with febrile UTI. Nasopharyngeal swab samples were collected at admission and tested for 16 respiratory viruses by nucleic acid detection methods. Respiratory symptoms were recorded, and blood MxA levels were determined. The median age of study children was 4 months (interquartile range, 2-14 months). A respiratory virus was detected in 17 (40%) children with febrile UTI. Of the virus-positive children with febrile UTI, 7 (41%) had simultaneous respiratory symptoms. Blood MxA levels were higher in virus-positive children with respiratory symptoms (median, 778 [interquartile range, 535-2538] mu g/L) compared to either virus-negative (155 [94-301] mu g/L, P < 0.001) or virus-positive (171 [112-331] mu g/L, P = 0.006) children without respiratory symptoms at presentation with febrile UTI. MxA differentiated virus-positive children with respiratory symptoms from virus-negative without symptoms by an area under the receiver operating characteristic curve of 0.96. Respiratory viruses were frequently detected in children with febrile UTI. In UTI with simultaneous respiratory symptoms, host antiviral immune response was demonstrated by elevated blood MxA protein levels. MxA protein could be a robust biomarker of symptomatic viral infection in children with febrile UTI.